“But Angels Don’t Have Wings”: Art, Religion, and Michelangelo’s Last Judgment in Gilio’s Dialogue on the Errors and Abuses of Painters - Russell, Anthony Presti (Religions, 2023)
This article provides a close reading of Giovanni Andrea Gilio’s critique of Michelangelo’s Last Judgment as presented in the Dialogue on the Errors and Abuses of Painters (1564). The dialogue has generally been taken as reflecting the emerging Counter-Reformation concerns regarding the indecorousness of contemporary religious art, concerns that led to the censoring of the Last Judgment’s nudes in 1564 after the Council of Trent’s decree on sacred images. One frequent justification for ecclesiastical oversight over the production of religious art was that artists such as Michelangelo had prioritized their art over its religious contents and devotional aims. Though Gilio’s work has been read as confirming this view, this essay argues that the various opinions expressed during the animated exchanges in the dialogue yield a set of nuanced and often innovative interpretations of the Last Judgment that resist a reductive dichotomy between art and religion. Whether intentionally or not, the dialogue conveys that by the time of Michelangelo, and perhaps because of Michelangelo, the forms of art and the contents of religion could not be so easily distinguished from each other, largely because the artist’s subjectivity blurred the boundaries between the two.